Trade Integration and Political Turbulence : Environmental Policy Consequences - Mani, Muthukumara; Fredriksson, Per. (Washington, D.C. : International Monetary Fund, 2001)
This paper seeks to contribute to the unresolved issue of the effect of economic integration on environmental policy. In particular, we discuss the joint impact of trade openness and political uncertainty. Our theory predicts that the effect of trade integreation on the environment is conditional on the degree of political uncertainty. Trade integration raises the stringency of environmental policies, but the effect is reduced when the degree of political uncertainty is great. Political uncertainty has a positive effect on environmental policy as it reduces lobbying efforts. Applying our model to a unique data set of primarily developing countries, the empirical findings support the theory and are robust under alterntive specifications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet